Netizen's Reception of Covid-19 Vaccination Policy Communication Through Instagram Account @kemenkes_ri - Supi Ainul Lutpi; Muhammad Febriansyah Rohimat; Alpin Alpin; Muhibudin Wijaya Laksana (Department of Public Administration, 2022)
The Covid-19 vaccination is one of the efforts of the Indonesian government to reduce morbidity and mortality due to the Covid-19 virus that hit Indonesia. In addition, this policy aims to create herd immunity in Indonesian society. The Ministry of Health of the Republic of Indonesia, as the leading sector of the Covid-19 vaccination policy in Indonesia, continues to disseminate policies so that target groups can see, understand, and prepare to implement this policy. The @kemenkes_ri account, managed by the Ministry of Health of the Republic of Indonesia, is used as one of the communication strategies in communicating this policy. Public acceptance of this policy is very diverse, as seen from the comments made in several publications at @kemenkes_ri about Covid-19 vaccination. This study aims to analyze the audience's acceptance and meaning of the Covid-19 vaccination policy information submitted through the @kemenkes_ri account. The method used in this research is using the qualitative interpretive method with a constructivist approach and reception analysis of Stuart Hall's encoding-decoding model. Data collection in this study was obtained by conducting semi-structured interviews and analyzing @kemenkes_ri Instagram feed uploads. Public acceptance of the Covid-19 vaccination policy in Indonesia is divided into three groups: hegemonic dominant positions, hegemonic negotiating positions, and hegemonic opposition positions. The three audience groups have different meaning constructions regarding the Covid-19 vaccination policy in Indonesia.